GENITAL WARTS INCIDENCE IN SAINT-PETERBURG, LENINGRADSKAYA REGION, KARELIYA REPUBLIC IN 2004–2013 - O. Yu. Stebelko (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. In 2012, information on vaccination against human papillomavirus infection was included in the form of state statistics number 5 «Information on vaccinations» in according to the Order of Rosstat number 645. In the world practice, as one of the early performance criteria of effectiveness of immunization against human papilloma virus is  morbidity rate by anogenital warts. The aim of this study was to investigate the regional characteristics of distribution of anogenital (venereal) warts before and in the initial periods of vaccination against human papillomavirus infection in three regions of the North-West Federal Regions — Saint Petersburg, Leningrad Oblast, Republic of Karelia. The period of retrospective epidemiological analysis was 10 years. There were significant differences in the levels and trends, morbidity by anogenital warts in general population and by gender. Moreover, different patterns of the frequency of disease among household contacts were revealed. In all three areas persons of 18–29 years old were identified as the risk group. The importance of determining the characteristics of epidemic processes for specified nosology in each territory has been demonstrated.